Deep Learning Algorithms for the Prediction of Posttransplant Renal Function in Deceased-Donor Kidney Recipients: A Preliminary Study Based on Pretransplant Biopsy - Luo, You; Liang, Jing; Hu, Xiao; Tang, Zuofu; Zhang, Jinhua; Han, Lanqing; Dong, Zhanwen; Deng, Weiming; Miao, Bin; Ren, Yong; Na, Ning (Frontiers in Medicine, 2022)
Background. Posttransplant renal function is critically important for kidney transplant recipients. Accurate prediction of graft function would greatly help in deciding acceptance or discard of allocated kidneys. Methods. Whole-slide images (WSIs) of hematoxylin-eosin (H&E)-stained donor kidney biopsies at 200x magnification between January 2015 and December 2019 were collected. The clinical characteristics of each donor and corresponding recipient were retrieved. Graft function was indexed with a stable estimated glomerular filtration rate (eGFR) and reduced graft function (RGF). We used a convolutional neural network (CNN)-based model including EfficientNet-B5, Inception-V3, and VGG19 for the prediction of these two outcomes. Results. In total, 219 recipients with H&E-stained slides of donor kidneys were included for analysis (biopsies from SCD/ECD was 191/28). The results showed distinct improvements in the prediction performance of the deep learning algorithm plus the clinical characteristics model. The EfficientNet-B5 plus clinical data model showed the lowest mean absolute error (MAE) and root mean square error (RMSE). Compared to the clinical data model, the area under the receiver operating characteristic curve (AUC) of the clinical data plus image model for eGFR classification increased from 0.69 to 0.83. The predictive performance for RGF also increased from 0.66 to 0.80. Gradient-weighted class activation mappings (Grad-CAMs) showed that the models localized the areas of the tubules and interstitium near the glomeruli, which were discriminative features for RGF. Conclusion. Our results preliminarily show that deep learning for formalin-fixed paraffin-embedded H&E-stained WSIs improves graft function prediction accuracy for deceased-donor kidney transplant recipients.